The influence of Shaykh Yusuf Al-Makassari's Sufi thought in the Malay world - Amy Nadirah Yacob (AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This study analyses the contributions, works, and some ṣufi thoughts of Shaykh Yusuf al-Makassari (d. 1699), a 17th-century Jawi scholar expert, and national activist. He remarks on his own legacy in the atmosphere of Muslim intellectual history. He learnt various ṣufi orders under learned teachers and was awarded the title of “Taj al-Khalwati” (the crown of the Khalwatiyah Order) by his ṣufi shaykh, Ayyub al-Khalwati. Hence, this thesis paper will shed light on selected views of Shaykh Yusuf al-Makassari in taṣawwuf to understand the trend of thought that he brought towards the Malay Muslims throughout the century. This thesis applies the qualitative method by referring to available primary and secondary sources. The study will refer to Shaykh Yusuf al-Makassari’s works entitled Zubdat al-Asrar fi taḥqiq ba’ḍ masharib al-Akhyar, Maṭalib al-Salikin, and Al-Nafḥah al-Saylaniyah fī al-Minḥat al-Raḥmaniyah. The findings show that al-Makassari’s unique and diverse view on tawhid is through the concept of al-Ma’iyyah al-Iḥaṭah (the All-Accompaniment and the All-Encompass of Allah) in terms of God’s knowledge, not in the physical unity of God and man as proposed by certain extreme views. This concept provides a balanced meaning in the face of outrageous notions about the existence of God. In relation to this view, the thesis also highlights the contributions of Shaykh Yusuf al-Makassari, who was actively involved in social and intellectual activities.